2015
DOI: 10.1007/s10735-014-9607-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical role of TCTP in epithelial ovarian cancer

Abstract: The aim of this study is to investigate the potential role and prognostic significance of translationally controlled tumor protein (TCTP) in human epithelial ovarian cancer (EOC). Western blot was used to evaluate the expression of TCTP in eight fresh EOC tissues. Immunohistochemistry was performed on formalin-fixed paraffin-embedded sections of 119 cases of ovarian cancers. Kaplan-Meier method indicated the relation between TCTP and EOC patients' overall survival rate. Starvation and re-feeding was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…Fortilin TCTP overexpression leads to systemic hypertension through its direct binding to and inhibition of Na,K-ATPase [95, 96], while it is not clear how fortilin TCTP contributes to pulmonary arterial hypertension [97]. Fortilin TCTP plays an important role in a number of malignant neoplasms including breast [27, 99, 100], gastric [102], colorectal [107, 108], liver [109], lung [110], oral [111], ovarian [112], and prostate [113, 114] cancers and central and peripheral nervous system tumors including glioma [19, 30, 116], neurofibromatosis [119], and neuroblastomas [120]. It is likely that tumorigenicity of fortilin TCTP is mediated by its ability to protect malignant cells against apoptosis [1, 1214, 16, 17, 20, 22, 55, 56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortilin TCTP overexpression leads to systemic hypertension through its direct binding to and inhibition of Na,K-ATPase [95, 96], while it is not clear how fortilin TCTP contributes to pulmonary arterial hypertension [97]. Fortilin TCTP plays an important role in a number of malignant neoplasms including breast [27, 99, 100], gastric [102], colorectal [107, 108], liver [109], lung [110], oral [111], ovarian [112], and prostate [113, 114] cancers and central and peripheral nervous system tumors including glioma [19, 30, 116], neurofibromatosis [119], and neuroblastomas [120]. It is likely that tumorigenicity of fortilin TCTP is mediated by its ability to protect malignant cells against apoptosis [1, 1214, 16, 17, 20, 22, 55, 56].…”
Section: Discussionmentioning
confidence: 99%
“…Chen and coworkers immunostained 119 formalin-fixed, paraffin-embedded epithelial ovarian cancer (EOC) tissues and found that fortilin TCTP expression was significantly and positively correlated with the International Federation of Gynecology and Obstetrics (FIGO) histological grade and shorter survival [112]. …”
Section: Fortilintctp In Human Diseases and Developmental Abnormalmentioning
confidence: 99%
“…Despite numerous reports suggesting relevant functions of TCTP in the context of tumor biology, and many findings highlighting that TCTP overexpression is associated with tumor progression and poor clinical outcome in many poorly differentiated tumors [4][5][6][7], the precise role of this protein is still a matter of debate. An important observation, which will be helpful to elucidate its implication in cell survival mechanisms, is that TCTP is a direct substrate of the serine/threonine kinase polo-like kinase 1 (PLK1), a crucial player in cell-cycle regulation during mitosis [8].…”
Section: Commentarymentioning
confidence: 99%
“…After transfected with sh Cyclin G1 or control-sh RNA 24 h, cells were seeded into 96-well plates at a concentration of 2 9 10 4 cells per well in volumes of 90 ll and grew overnight (Chen et al 2015). 10 ll CCK8 reagents (Dojindo, Kumamoto, Japan) were then added into every well at different time points and then incubated for 2 h in dark environment.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%